UOW-SHEF: SimpLex – Lexical Simplicity Ranking based on Contextual and Psycholinguistic Features - Jauhar, Sujay Kumar; Specia, Lucia (Proceedings of the 6th International Workshop on Semantic Evaluation (SemEval 2012), 2012)
This paper describes SimpLex, a Lexical Simplification system that participated in the English Lexical Simplification shared task at SemEval-2012. It operates on the basis of a linear weighted ranking function composed of context sensitive and psycholinguistic features. The system outperforms a very strong baseline, and ranked first on the shared task.